Kinetic correlations of gas-liquid mass transfer coefficient and oxygen uptake rate of heterologous protein cultivation by sonobioreactor - Ajit, Azilah (2016)
Sonobioreactor in this study is an integration system which includes the use of a sonicator with a bioreactor by the assembly of a peristaltic pump. The sonobioreactor was being applied to the production of a heterologous protein, lipase by the expression of a recombinant E. coli. The first objective of this study was to transform all the recombinant E. coli into BL21 host. The BL21 was found successful in carrying pTrcHis and pUC8, both carrying lipase gene from Staphylococcus hyicus and Rhizopus oryzae, respectively. Second objective is to investigate the characteristics of 2-L sonobioreactor for the use of recombinant E. coli cultivation. The sonobioreactor has shown some improvement of gas-liquid transfer (kLa} compared to the standalone system. Third objective is to determine the expression of lipase and plasmid stability of recombinant E. coli under sonicated and non-sonicated ultrasound regimens. The non-sonicated cultivation has shown higher lipase activity compared to the sonicated cultivation. The gradual sonication duty cycle has shown images of deformed cells of recombinant E. coli at 9K total magnification via SEM. Performances and kinetics of bioprocesses outcomes in this study may contribute to the current modelling of E. coli fermentations, especially for the recombinant protein production.